1981
DOI: 10.1007/bf02541591
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene alcohols and sterols of Spanish olive oil

Abstract: Nine Spanish olive oils, including three each of virgin (pressed oil), refined virgin, and B‐residue (solvent‐extracted pomace oil) oils from different commercial sources, have been analyzed for their unsaponifiable matter (USM). Four sterolic fractions separated from the oils have been analyzed by preparative thin‐layer chromatography (TLC); these fractions are triterpene alcohols, 4‐methylsterols, sterols and triterpene dialcohols. The compositions of the four sterolic fractions were determined as their acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 28 publications
5
30
0
4
Order By: Relevance
“…The levels of Δ5-avenasterol in olive oil samples were relatively lower than the values reported previously by Ben Temime et al (2008); Rivera del Alamo et al (2004) and they are in the range of 1.43% (Mari cultivar of Gilvan) to 6.39% (Zard cultivar of Fadak), although they are in agreement with the results obtained by Itoh et al (1981).The Δ5-avenasterol content of the Zard variety of Fadak (6.39%) was significantly (P<0.05) higher than the other cultivars and the Mari variety of Fadak (1.78%) and Gilvan (1.43%) were significantly (P<0.05) the lowest ones. Wang et al (2002) reported that Δ5-avenasterol at elevated temperatures exhibited antioxidant activity and improved oxidative stability in olive oil under frying condition.…”
Section: Total Sterolssupporting
confidence: 90%
“…The levels of Δ5-avenasterol in olive oil samples were relatively lower than the values reported previously by Ben Temime et al (2008); Rivera del Alamo et al (2004) and they are in the range of 1.43% (Mari cultivar of Gilvan) to 6.39% (Zard cultivar of Fadak), although they are in agreement with the results obtained by Itoh et al (1981).The Δ5-avenasterol content of the Zard variety of Fadak (6.39%) was significantly (P<0.05) higher than the other cultivars and the Mari variety of Fadak (1.78%) and Gilvan (1.43%) were significantly (P<0.05) the lowest ones. Wang et al (2002) reported that Δ5-avenasterol at elevated temperatures exhibited antioxidant activity and improved oxidative stability in olive oil under frying condition.…”
Section: Total Sterolssupporting
confidence: 90%
“…The 50% inhibitory concentration (IC 50 ) values were calculated by interpolation from the linear regression curve. Table 1 summarized the inhibitory effect against HIV-1 RT of 55 triterpenoids consisting of four cycloartanes (1-4), three lanostanes (5-7), three euphanes (8-10), two tirucallanes (11,12), six dammaranes (13)(14)(15)(16)(17)(18), one cucurbitane (19), eleven lupanes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), seven oleananes (31)(32)(33)(34)(35)(36)(37), five ursanes (38)(39)(40)(41)(42), six multifloranes (43- (14), and ursolic acid (41; 6.4 µM) were shown to possess potent inhibitory effect against HIV-1 RT in this and in our recent studies (14), some synthetic derivatives of 25 (4,(16)(17)(18)(19)(20)(21), 32 (19), and 41 (22) have been reported to show strong anti-HIV-1 activity by inhibiting HIV-1 replication in H9 lymp...…”
Section: Methodsmentioning
confidence: 99%
“…The olive tree leaf and olive oil have been known for a long time to contain a variety of sterols and triterpenoids, including erythrodiol, oleanic acid and maslinic acid, which are oxygenated derivatives of b-amyrin [17][18][19]. However, very little attention has been paid so far to sterol and triterpenoid metabolism in developing drupes, mainly because of the low content of these compounds (around 1%) compared to triacylglycerols (TAGs) and the long maturation period of the olive fruit (6-7 months).…”
Section: Introductionmentioning
confidence: 99%